Interrater Reliability of Qualitative Ultrasound Assessment of Gastric Content in the Third Trimester of Pregnancy. Issue 4 (December 2015) - Arzola, C.; Cubillos, J.; Perlas, A.; Downey, K.; Carvalho, J.C.
Abstract : ( Br J Anaesth . 2014;113(6):1018–1023)